The role of maternal-specific H3K9me3 modification in establishing imprinted X-chromosome inactivation and embryogenesis in mice - Fukuda, Atsushi (Nat Commun, 2014)
Maintaining a single active X-chromosome by repressing Xist is crucial for embryonic development in mice. Although the Xist activator RNF12/RLIM is present as a maternal factor, maternal Xist (Xm-Xist) is repressed during preimplantation phases to establish imprinted X-chromosome inactivation (XCI). Here we show, using a highly reproducible chromatin immunoprecipitation method that facilitates chromatin analysis of preimplantation embryos, that H3K9me3 is enriched at the Xist promoter region, preventing Xm-Xist activation by RNF12. The high levels of H3K9me3 at the Xist promoter region are lost in embryonic stem (ES) cells, and ES-cloned embryos show RNF12-dependent Xist expression. Moreover, lack of Xm-XCI in the trophectoderm, rather than loss of paternally expressed imprinted genes, is the primary cause of embryonic lethality in 70–80% of parthenogenotes immediately after implantation. This study reveals that H3K9me3 is involved in the imprinting that silences Xm-Xist. Our findings highlight the role of maternal-specific H3K9me3 modification in embryo development.